One-Pot Synthesis and Characterization of Novel Shape-Memory Poly(ε-Caprolactone) Based Polyurethane-Epoxy Co-networks with Diels–Alder Couplings - Czifrák, Katalin (Polymers (Basel), 2018)
The present work aimed at the preparation and investigation of different epoxy-polyurethane (EP-PU) co-networks. The EP-PU co-networks were obtained by applying two different synthetic strategies, in which the coupling element, the Diels–Alder (DA) adduct, was prepared previously or formed “in situ” in the reaction between furan functionalized polyurethane and furfuryl amine-diglycidyl ether bisphenol-A oligomers (FA_DGEBA). For the synthesis of these EP-PU networks, poly(ε-caprolactone)-diol (PCD, M(n) = 2 kg/mol) and poly(ε-caprolactone) (PCL) with different molecular weights (M(n) = 10, 25 and 50 kg/mol) and 1,6-hexamethylenediisocyanate (HDI) were used. The EP-PU co-networks were characterized by Attenuated Total Reflectance Fourier-Transform Infrared spectroscopy (AT-FT-IR), differential scanning calorimetry (DSC) and dynamical mechanical analysis (DMA). Scanning electron microscopy (SEM) was applied to assess the morphology of the EP-PU samples. It was demonstrated that the stress–strain curves for the EP-PUs could be interpreted based on the Standard Linear Solid (SLS) model. The DMA traces of some EP-PUs (depending on the composition and the synthetic method) revealed a plateau-like region above the melting temperature (T(m)) of PCL confirming the presence of cross-linked structure. This feature predicted shape memory (SM) behavior for these EP-PU samples. Indeed, very good shape fixity and moderate shape recovery were obtained. The shape recovery processes of these EP-PU samples were described using double exponential decay functions.